Neutrophil-to-Lymphocyte Ratio, Lymphocyte-to-Monocyte Ratio and Platelet-to-Lymphocyte Ratio as Predictors of Short- and Long-Term Outcomes in Ischemic Stroke Patients with Atrial Fibrillation - Guo J; Wang D; Jia J; Zhang J; Liu Y; Lu J; Zhao X; Yan J (Dove Medical Press, 2024)
Jiahuan Guo,1 Dandan Wang,1 Jiaokun Jia,1 Jia Zhang,1 Yanfang Liu,1 Jingjing Lu,1,2 Xingquan Zhao,1- 4,* Jing Yan1,* 1Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China; 2China National Clinical Research Center for Neurological Diseases, Beijing Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China; 3Research Unit of Artificial Intelligence in Cerebrovascular Disease, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 4Center of Stroke, Beijing Institute for Brain Disorders, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xingquan Zhao; Jing Yan, Email zxq@vip.163.com; joyce_yj@163.comPurpose: Inflammatory response plays essential roles in the pathophysiology of both ischemic stroke and atrial fibrillation (AF). We aimed to investigate whether composite inflammatory markers, including neutrophil to lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR) and platelet-to-lymphocyte ratio (PLR), can serve as early predictors of short- and long-term outcomes in ischemic stroke patients with AF.Patients and Methods: Ischemic stroke patients with AF were enrolled in this cohort study. The primary outcome was 1-year functional dependence or death (modified Rankin scale (mRS) score 3- 6). Secondary outcomes included hemorrhagic transformation (HT) and early neurological deterioration (END, increase in the National Institutes of Health Stroke Scale (NIHSS) ≥ 4 within 7 days). Partial correlations were performed to assess the correlation between systemic inflammation markers and admission NIHSS scores. Univariate and multivariate logistic analyses were performed to investigate whether systemic inflammatory markers were independent predictors of adverse outcomes.Results: A total of 408 patients were included. Partial correlation analysis revealed statistically significant but weak correlations between the NLR (r = 0.287; P < 0.001), PLR (r = 0.158; P = 0.001) and admission NIHSS score. Compared with patients without HT or END, patients who developed HT or END had higher NLR and PLR, and lower LMR. Patients in the functional dependence or death group had significantly higher NLR and PLR, and lower LMR than those in the functional independence group (all P < 0.001). Multivariate logistic analysis indicated that NLR, LMR and PLR were independent predictors of HT (OR = 1.069, 0.814 and 1.003, respectively), END (OR = 1.100, 0.768 and 1.006, respectively) and adverse 1-year functional outcome (OR = 1.139, 0.760 and 1.005, respectively).Conclusion: NLR, LMR and PLR were independent predictors for in-hospital HT, END and long-term functional outcome in ischemic stroke patients with AF. Close monitoring of these inflammatory markers may help guide risk stratification and clinical treatment strategies.Keywords: inflammation, ischemic stroke, atrial fibrillation, hemorrhagic transformation, early neurological deterioration, functional outcome